EFEKTIVITAS EKSTRAK TEH HIJAU (Camellia sinensis L.) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PUASA TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR WISTAR YANG DIINDUKSI ALOKSAN - Hafshah (2020)
The prevalence of diabetes mellitus (DM) is increasing from year to year. Indonesia is the fourth highest number of DM sufferers in the world, with a death toll of 1,2 million in 2012. Because of the high prevalence, it is necessary to find alternative treatments that are more effective, one of which is green tea (Camellia sinensis L.) which is antihyperglycemic. This study aims to determine the effectiveness of green tea extracts on decreasing fasting blood glucose (KGDP) levels in alloxan-induced white male Wistar rats. Samples were 30 male rats, aged 8-12 weeks, weight ± 200 g. Rats were grouped into 6 groups with the first group (K1) as normal control, the second group (K2) induced alloxan, the third group (K3) induced alloxan and given glibenclamide, the fourth group (K4) induced alloxan and given green tea extract at a dose of 200 mg/kg, the fifth group (K5) was induced by alloxan and 400 mg/kg was given green tea extract, and the sixth group (K6) was induced by alloxan and 800 mg/kg was given green tea extract. Giving green tea extract was given for 16 days orally, then re-examined KGDP from the rat's tail. The paired T test results showed the effectiveness of green tea extract on the reduction of hyperglycemia rat KGDP (p = 0,000). One Way Anova Test, there is an effectiveness of green tea extract on the reduction of KGDP (p = 0,000). Bonferroni's post hoc test showed that giving 800 mg / kgBB of green tea extract was the best in reducing KGDP close to normal (p = 0,000). Keywords : Alloxan, hyperglycemia, FBG level, green tea,